The body lies - Baker, Jo (Alfred A. Knopf, 2019)
"A dark, thrilling new novel from the best-selling author of Longbourn: a work of riveting psychological suspense that grapples with how to live as a woman in the world--or in the pages of a book--when the stakes are dangerously high. When a young writer accepts a job at a university in the remote English countryside, it's meant to be a fresh start, away from the bustle of London and the scene of a violent assault she is desperate to forget. But despite the distractions of her new life and the demands of single motherhood, her nerves continue to jangle. To make matters worse, during class a vicious debate about violence against women inflames the tensions and mounting rivalries in her creative writing group. When a troubled student starts turning in chapters that blur the lines between fiction and reality, the professor recognizes herself as the main character in his book--and he has written her a horrific fate. Will she be able to stop life imitating art before it's too late? At once a breathless cat-and-mouse game and a layered interrogation of the fetishization of the female body, The Body Lies gives us an essential story for our time that will have you checking the locks on your doors"--